PENGARUH JUMLAH PENDUDUK DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA PALEMBANG (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The purpose of this research is to determine the influence of population andbalance fund on the economic growth of Palembang City in 2001-2018 period. Theanalytical tool used is multiple linear regression. The results of this study aresimultaneously and partially there has no significant effect of population and balancefund on the economic growth of Palembang City in 2001-2018. The coefficient ofdetermination (R Square) is 0.119 which means the population and balance fundshave a contributing effect on variations in changes in the economic growth ofPalembang City in 2001-2018 only by 11.9% while the remaining 88.1% isinfluenced by other variables which was not included in this research.